Evasion, failure and school exclusion - Moraes, Andrea Maria Monteiro de; Oliveira, Lívia Ferreira de; Moraes, Nair Maria Monteiro de; Fiori, Taís Dayane; Silvestre, Vanessa Souto; Salomão, Maria Aparecida Vieira (Revista Hipótese, 2016)
This paper discusses a reflection about the inefficiency of basic education in Brazil, which promotes and leads to evasion, failure and school exclusion. This subject has been discussed in several studies on education systems and public policies of the country. It is a matter of great complexity, seek to identify the reasons that daunt million school students is the first step, recognizing that there is no one responsible, but a number of motivators that leverage the negative statistics of education failure. Thus, this study deals possible causes and consequences of high rates of evasion and neglect in basic education that drives and encourages school failure.
Keywords: Evasion; Failure; Abandonment; Exclusion